EFFECT OF THE BODY CONDITION SCORE ON SOME REPRODUCTION AND MILK YIELD TRAITS OF SWEDISH RED AND WHITE COWS - B. Bayram; V. Aksakal; Ö. Akbulut (Journal of Animal and Plant Sciences, 2012)
This study examined the effect of body condition score (BCS) at calving and during the first month of lactation on some  reproduction and milk yield traits of Swedish Red and White (SRW) cows organically raised in Turkey. For this purpose, SRW cows divided two groups, named as thin (BCS <3.00) and moderate (BCS ≥ 3.00). The actual milk yield (815 kg) and 305 day daily milk yield (736 kg) of cows with low condition score at calving were significantly (P<0.01) higher than those with moderate condition score. The BCS at calving did not have an effect on the lactation length, peak daily milk yield and days to attain peak milk yield. The condition score obtained in the first month of lactation only affected the peak daily milk yield (P<0.05), while its impact on the other characteristics was non-significant. The service period of the cows with low condition score at calving was significantly longer (19.9 day) and their number of services per conception was significantly lower (0.37 units) (P<0.05) than moderate group. The condition loss was calculated as 0.0137 units in the thin group and 0.2290 units in the moderate group and this differences were significant (P<0.01) during the first 30 day period of lactation. The phenotypic correlation between BCS at calving and milk yield traits were negative and significant (P<0.01). According to this relationship, actual milk yield (r=-0.208), 305 day milk yield (r=-0.248) and peak daily milk yield (r=-0.251) decreased significantly (P<0.01) with the increase in the BCS at calving. The service periods of cows with low condition scores at calving were significantly longer (P<0.01).
Keywords: Swedish Red; body condition score; organic dairy farming; milk yield; reproduction